ROLE OF PACKAGINGAND LABELING ON PAKISTANI CONSUMERS PURCHASE DECISION - Raheem, Ahmed Rizwan; Nawaz, Ahmad; Vishnu, Parmar; Imamuddin, Khoso (European Scientific Journal, ESJ, 2014)
The objective of this study is to determine role of packaging and labeling on Pakistaniconsumer’s Purchase decisions. The purpose of this research is to examine the essential factors, which are driving the success of a brand and how these factors motivate the consumers while he/she involves in purchase decisions for any particular brands of FMCGs goods. This research also identified the relationship between the dependent and independent variables who are main contributors in this whole purchase and motivation behavior. This is the primary research and data has been collected through questionnaire and for analysis purpose SPSS software has been used. In this study samples of 100 respondents has been collected and tested the reliability of the model. According to the finding of the research study, it has been observed that the packaging and Labeling are the most important factors. It is further concluded that the packaging elements like its Color, Packaging material, Design of Wrapper and innovation are more important factors while consumers making any buying decision. Finally it has also been concluded that the Packaging is one of the most important and powerful factor, which influences consumer’s purchase decision.